2015
DOI: 10.1007/s10295-014-1559-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient expression of nattokinase in Bacillus licheniformis: host strain construction and signal peptide optimization

Abstract: Nattokinase (NK) possesses the potential for prevention and treatment of thrombus-related diseases. In this study, high-level expression of nattokinase was achieved in Bacillus licheniformis WX-02 via host strain construction and signal peptides optimization. First, ten genes (mpr, vpr, aprX, epr, bpr, wprA, aprE, bprA, hag, amyl) encoding for eight extracellular proteases, a flagellin and an amylase were deleted to obtain B. licheniformis BL10, which showed no extracellular proteases activity in gelatin zymog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 31 publications
0
64
0
Order By: Relevance
“…In this study, both nattokinase and α-amylase were selected as prototype target proteins for secretion to evaluate the function of SppA and TepA in B. licheniformis BL10, derived from the native strain B. licheniformis WX-02 [7]. Our results identified and confirmed that SppA is the main SPP for protein secretion, and the concentrations of total extracellular proteins and target proteins increased significantly for a strain overexpressing sppA .…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…In this study, both nattokinase and α-amylase were selected as prototype target proteins for secretion to evaluate the function of SppA and TepA in B. licheniformis BL10, derived from the native strain B. licheniformis WX-02 [7]. Our results identified and confirmed that SppA is the main SPP for protein secretion, and the concentrations of total extracellular proteins and target proteins increased significantly for a strain overexpressing sppA .…”
Section: Introductionmentioning
confidence: 58%
“…Nattokinase expression vector pP43SacCNK was made in a previous study [7], and the α-amylase expression vector pHY-amyL harboring P43 promoter (K02174.1), amyL (FJ556804.1) coding for α-amylase (containing its own signal peptide and terminator) was verified by DNA sequence. The pP43SacCNK and pHY-amyL plasmids were individually electro-transferred into the parental strain B. licheniformis BL10, as well as the SPP gene deficient strains BL10S and BL10T.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations